PHT3D‐UZF: A Reactive Transport Model for Variably‐Saturated Porous Media. Issue 1 (27th January 2015) - Wu, Ming Zhi; Post, Vincent E.A.; Salmon, S. Ursula; Morway, Eric D.; Prommer, Henning
Abstract: A modified version of the MODFLOW/MT3DMS‐based reactive transport model PHT3D was developed to extend current reactive transport capabilities to the variably‐saturated component of the subsurface system and incorporate diffusive reactive transport of gaseous species. Referred to as PHT3D‐UZF, this code incorporates flux terms calculated by MODFLOW's unsaturated‐zone flow (UZF1) package. A volume‐averaged approach similar to the method used in UZF‐MT3DMS was adopted. The PHREEQC‐based computation of chemical processes within PHT3D‐UZF in combination with the analytical solution method of UZF1 allows for comprehensive reactive transport investigations (i.e., biogeochemical transformations) that jointly involve saturated and unsaturated zone processes. Intended for regional‐scale applications, UZF1 simulates downward‐only flux within the unsaturated zone. The model was tested by comparing simulation results with those of existing numerical models. The comparison was performed for several benchmark problems that cover a range of important hydrological and reactive transport processes. A 2D simulation scenario was defined to illustrate the geochemical evolution following dewatering in a sandy acid sulfate soil environment. Other potential applications include the simulation of biogeochemical processes in variably‐saturated systems that track the transport and fate of agricultural pollutants, nutrients, natural and xenobiotic organic compounds and micropollutants such as pharmaceuticals, as well as the evolution of isotope patterns.